The Energy Transition Is Just the Tip of the Iceberg: Changes in Understanding Modern Democracy in the Context of the Climate Crisis - Kamiński, Bartosz (Stan Rzeczy, 2025)
The aim of this article is to consider the liberal perspective and the de-growth perspective on capitalism, the climate crisis, and energy consumption. According to proponents of capitalism, solving the climate crisis needs to be done in terms of “green growth.” More radical thinkers argue that the problem is not the source of energy but rather that its consumption is subordinated to economic growth. Therefore, they propose changing the energy consumption strategy from a model aimed at infinite profit to one focused on ensuring universal well-being. This article outlines selected basic socio-political issues related to moving away from economic growth and the possibilities for redefining the understanding of democracy. Abandoning the concept of economic growth also presents an opportunity for transformations within political ontology – the possibility of viewing society as a multitude without the privileged position of the human. The article thus also shows the similarities between ontological resolutions and the changes that need to occur in understanding the climate crisis, and thereby depicts the need for changes that are far more complex than merely making capitalism “greener.”